Correlation Between Inflammatory Markers and Pathogenic Bacteria in Children’s Winter Respiratory Infections in Xinjiang - Wang L; Wang W; Wang J; Zhu L; Luo J (International Journal of General Medicine)
Lixia Wang,1,* Wei Wang,2,* Jian Wang,1 Ling Zhu,1 Jianjiang Luo1 1Department of Respiratory and Critical Care Medical Department Infectious Diseases Ward, The Traditional Chinese Medicine Hospital Affiliated to Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Affiliated Traditional Chinese Medicine Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianjiang Luo, Department of Respiratory and Critical Care Medical Department infectious diseases Ward, The Traditional Chinese Medicine Hospital Affiliated to Xinjiang Medical University, No. 116 Huanghe Road, Shayibake District, Urumqi, Xinjiang, People’s Republic of China, Tel +86013999946655, Email ljj.781201@163.comBackground: This study examines the distribution characteristics of pathogenic bacteria in respiratory infections and their relationship with inflammatory markers to guide clinical drug use.Methods: We selected 120 patients with lower respiratory tract infection in the electronic medical record system of Xinjiang Provincial People’s Hospital from March 2019 to March 2023 for a case-control study. Using Indirect Immunofluorescence Antibody test(IFA), blood routine, C-reactive Protein (CRP), and High-sensitivity C-reactive Protein(hsCRP), we detected nine respiratory pathogens (Respiratory syncytial virus; Influenza A virus; Influenza B virus; Parainfluenza virus; Adenovirus; Mycoplasma pneumoniae; Chlamydia pneumoniae; Legionella pneumophila type 1; Rickettsia Q) in all patients and analyzed their distribution and correlation. The patients were divided into three groups [Respiratory Syncytial Virus Immunoglobulin M(RSV-IgM) positive group A, Mycoplasma Immunoglobulin M(MP - IgM) positive group B, antibody - negative group with elevated hsCRP, 40 patients each]. We compared differences in hsCRP, platelet count, White Blood Cells(WBC), and Neutrophil(NE) among the groups.Results: We conducted a systematic sorting and analysis of variables exhibiting significant differences. The results of the multivariate logistic regression analysis indicated that inflammatory markers, including white blood cell count (WBC) (OR 3.85, 95% CI: 1.116– 1.623), neutrophils (NE) (OR 2.26, 95% CI: 1.091– 1.312), high-sensitivity C-reactive protein (HsCRP) (OR 1.95, 95% CI: 1.068– 14.640), lymphocytes (OR 1.30, 95% CI: 1.045– 1.134), platelet count (OR 1.34, 95% CI: 1.625– 2.760), and C-reactive protein (CRP) (OR 3.80, 95% CI: 1.232– 2.379), were significantly associated with the presence of pathogenic bacteria.Conclusion: There was significant correlation between inflammatory markers and pathogenic bacteria in patients with lower respiratory tract infection in Xinjiang region.Keywords: correlation, inflammatory markers, lower respiratory tract infection, pathogenic bacteria